Динамика религиозного экстремизма в России в богословских, правовых и психологических подходах к социальной и личностной; Dynamics of Religious Extremism In Russia In Theological, Legal and Psychological Approaches to Social and Personal - Maulana, Amy; Buana, Dana Riksa; Magomedovich, Abdulaev Ibragimgadzhi (Jurnal Cita Hukum, 2022)
After the collapse of the Soviet Union in the post-Soviet era, a spiritual vacuum was formed in the conditions of deterioration of the political and economic situation. In the North Caucasus region, during the formation of the Russian state, it was quickly filled with religion: Wahhabism emerged, spread and increasingly declared itself religious extremism. Several terrorist attacks have occurred not only in the North Caucasus, but also in several Russian cities. This article describes the dynamics of religious extremism in Russia from the point of view of the theological, legal and psychological approach to social and personal. With regard to the soft approach, Russia can implement programs of deradicalization and counter-radicalization. In this regard, Russia may create a National Agency for Combating Terrorism and launch a deradicalization project and create a Deradicalization Center for convicted terrorists. Efforts to prevent the development of religious extremism in Russia are being undertaken not only with a legal approach, but also with a theological approach, since it is connected with Islamic concepts.